Waste ceramic as low cost and eco-friendly materials in the production of sustainable mortars. (1st September 2020) - Samadi, Mostafa; Huseien, Ghasan Fahim; Mohammadhosseini, Hossein; Lee, Han Seung; Abdul Shukor Lim, Nor Hasanah; Tahir, Mahmood Md; Alyousef, Rayed
Abstract: Reducing the use of natural resources and ensuring proper reuse of industrial wastes are among the most practical potential solutions for sustainable development and a cleaner environment. The generation and disposal of waste materials that cause severe ecological impacts must be inhibited. Based on these ideas, we propose the utilisation of ceramic waste, which is inexpensive, abundant, and environmentally friendly, as a partial replacement for cement and fine aggregates in the preparation of some new types of mortars. This study investigates the long-term performance, mechanical properties, and durability of a mortar comprising ceramic waste as supplementary cementitious material and ceramic particles as fine aggregates. In addition, the environmental benefits of sustainable mortar are assessed. The structure, morphology, and thermal traits of the designed mixes are characterised using scanning electron microscopy (SEM), thermogravimetric analysis (TGA), differential thermal analysis (DTA), X-Ray Diffraction (XRD), and Fourier-transform infrared spectroscopy (FTIR) measurements. The results of this study indicate that the utilisation of ceramic waste as both a binder and a fine aggregate source significantly improved the compressive strength of the mortar and provided higher resistance against adverse environmental conditions. The positive interaction between ceramic waste and fine aggregates enabled a higher level of crystalline formation and, therefore, a reduction in porosity and cracking. In summary, it was demonstrated that ceramic waste blended mortars displayed enhanced performance and energy-saving qualities, which are both technically and environmentally useful and may lead to lower construction costs and increased sustainability. Highlights: The compressive strength of the mortars was enhanced via ceramic waste inclusion. Blended cement containing ground ceramic improves mortar resistance to sulphate. Use of ceramic waste in mortar provides practical and environmental benefits. Mortar containing ceramic waste lowers greenhouse gas emissions.